Heat stress induced cell death mechanisms in hepatocytes and hepatocellular carcinoma: In vitro and in vivo study. Issue 4 (18th March 2014) - Thompson, Scott M.; Callstrom, Matthew R.; Butters, Kim A.; Knudsen, Bruce; Grande, Joseph P.; Roberts, Lewis R.; Woodrum, David A.
ABSTRACT Background and Objective The aims of the present study were to investigate the thermal‐dose dependent effect of heat stress on hepatocyte and HCC cell death mechanisms using clinically relevant experimental heat stress conditions in vitro and to investigate apoptotic cell death induced by laser thermal ablation in vivo. Study Design/Materials and Methods Institutional Animal Care and Use Committee approved all studies. Hepatocyte and HCC cell lines were heat stressed from 37 to 60°C for 2 or 10 minutes and assessed for viability, cytotoxicity and caspase‐3/7 activity at 6 and/or 24 hours post‐treatment (N = 3). Viability experiments were repeated with the RIPK1 inhibitor Necrostatin‐1 to block necroptosis (N = 3). Rats with orthotopic HCC tumors stably expressing luciferase (N1S1luc2) were randomized to US‐guided laser ablation (3W‐45s for an intentional partial ablation; N = 6) or sham (N = 6) and followed by post‐ablation caspase‐3/7 bioluminescence imaging at 6 and 24 hours and cleaved caspase‐3 immunostaining. P < 0.05 was considered statistically significant. Results Heat‐stress induced apoptosis and necrosis in hepatocytes and HCC cells in a thermal dose and cell‐type dependent manner. Inhibition of RIPIK1‐mediated necroptosis induced a significant, differential increase in HCC cell viability under physiologic and hyperthermic heat stress (P < 0.001). Intentional partial laser thermal ablation induced a significant increase in caspase‐3/7 activity in the laser versus sham ablation groups at both 6 hours (10.1‐fold, P < 0.01) and 24 hours (16.7‐fold, P < 0.02). Immunohistochemistry confirmed increased cleaved caspase‐3 staining at the tumor ablation margin 24 hours post‐ablation. Conclusions Both regulated and non‐regulated cell death mechanisms mediate heat stress‐induced HCC cell killing and vary between hepatocytes and HCC subtypes. Apoptosis is a significant mechanism of cell death at the HCC tumor ablation margin. Lasers Surg. Med. 46:290–301, 2014. © 2014 Wiley Periodicals, Inc.